Contemporary problems in medicine – technique or ethics? - Płazak, Wojciech (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
Technical and pharmacological revolution in contemporary medicine has not resolved the ethical problems that seem to be more relevant today than ever before. Most of the papers that concern medical ethics focus on `great’ problems, such as human genome sequencing, organizms cloning and quantitative or qualitative interference with life creation. This article, however, describes practical ethical problems that the doctors face in every-day practice. First of all, the problem of how thestandards of prophilaxis and treatment should be established when the costs exceed financial possibilities of a health system. Secondly, how to face the problem of rare diseases when the cost of a single patient treatment may be equal to the whole medical department budget. Thirdly, how to procede with elderly patients with multiple diseases qualified for invasive procedures. All of these examples share the common base: in these cases the technical equipment is at our disposal, yet we cannot or we do not want to use it.